Erratum to non-homologous end-joining protein expression screen from radiosensitive cancer patients yields a novel DNA double strand break repair phenotype - McKay, Michael J.; Goh, Su Kah; McKay, Jeremy N.; Chao, Michael; McKay, Timothy M. (Annals of Translational Medicine, 2017)
Non-homologous end-joining protein expression screen from radiosensitive cancer patients yields a novel DNA double strand break repair phenotype